STUDI EMPIRIK TENTANG STRUKTUR MODAL PADA INDUSTRI MANUFAKTUR DI INDONESIA - Toto Suharmanto (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
This study aims to analyze the determinants of capital structure in manufacturing industries listed on the Indonesia Stock Exchange. The data used is taken from the financial statements of manufacturing companies whose shares are still actively traded on the Indonesia Stock Exchange. The variables used are profitability proxied by return on equity (ROE), sales growth, asset structure, liquidity proxied by current ratio (CR), tax, business risk and capital structure proxied by debt-to-equity ratio (DER). Sampling using purposive sampling method, and data analysis using multiple regression. The results show that liquidity (current ratio) has a negative effect on capital structure at a significance of less than 1%. Meanwhile, profitability (return on equity), sales growth, asset structure, tax and business risk have no effect on capital structure. Keywords: profitabilias, sales growth, asset structure, liquidity, tax, business risk, capital structur